2020
DOI: 10.1371/journal.pone.0237073
|View full text |Cite
|
Sign up to set email alerts
|

The Twitter parliamentarian database: Analyzing Twitter politics across 26 countries

Abstract: This article introduces the Twitter Parliamentarian Database (TPD), a multi-source and manually validated database of parliamentarians on Twitter. The TPD includes parliamentarians from all European Free Trade Association countries where over 45% of parliamentarians are on Twitter as well as a selection of English-speaking countries. The database is designed to move beyond the one-off nature of most Twitter-based research and in the direction of systematic and rigorous comparative and transnational analysis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 79 publications
(52 reference statements)
0
41
0
Order By: Relevance
“…The entire stream of tweets from 590 British Parliamentarians was gathered using Twitter’s Streaming API from June 1, 2017 until the election of the new parliament on December 12, 2019 ( van Vliet et al, 2020 ). During this time, there were parliamentary deadlocks on what exactly would happen in the divorce process with the EU.…”
Section: Methodsmentioning
confidence: 99%
“…The entire stream of tweets from 590 British Parliamentarians was gathered using Twitter’s Streaming API from June 1, 2017 until the election of the new parliament on December 12, 2019 ( van Vliet et al, 2020 ). During this time, there were parliamentary deadlocks on what exactly would happen in the divorce process with the EU.…”
Section: Methodsmentioning
confidence: 99%
“…Among the different communication layers (relations, retweets, and mentions) on Twitter, we have focused on MPs’ mentions because this network better reflects cross-party and cross-ideological connections (Esteve Del Valle & Borge Bravo, 2018a) as well as MPs’ personalized communication behavior (Thamm & Bleier, 2013) and is more decentralized than following–follower and retweet networks (Conover et al, 2011; Hsu & Park, 2012; Yoon & Park, 2014). Furthermore, previous research has shown that politicians actively use mentions to converse with each other (Esteve Del Valle & Borge Bravo, 2018a; van Vliet et al, 2020), mostly to criticize members of other parties, that is, “point out any apparent mistakes, misbehavior or false statement of their rivals” (Laaksonen et al, 2017, p. 117). Last, compared to the broadcasting practices of parliamentarians in other countries (e.g., the United Kingdom or the United States), Dutch MPs are highly conversational on Twitter, notably vis-à-vis other members of the Tweede Kamer , the Dutch House of Representatives (see Tromble, 2018).…”
mentioning
confidence: 99%
“…As a result, in the last several years, the use of big data analytics to make sense of the tremendous volume of first-hand user-generated information accumulated on social media is becoming increasingly popular [e.g., 3 , 16 , 17 19 ]. Amongst social media platforms, Twitter has been the platform of most interest to researchers [ 20 ].…”
Section: Background and Related Workmentioning
confidence: 99%